(untitled) - Millon, Theodore (Hoboken, N.J., 2007)
A revolutionary, personalized psychotherapy approach for the treatment of Axis II personality disorders, by renowned expert Dr. Theodore Millon Acknowledging the primacy of the whole person, Overcoming Resistant Personality Disorders: A Personalized Psychotherapy Approach takes into account all of the complexities of human nature--family influences, culture, neurobiological processes, unconscious memories, and so on--illustrating that no part of human nature should lie outside the scope of a clinician's regard.
Keywords: Personality disorders,Personality,Personality Disorders,Psychotherapy; Therapy,Methods